2013
DOI: 10.1093/ije/dyt173
|View full text |Cite
|
Sign up to set email alerts
|

Substance use disorders and psychiatric comorbidity in mid and later life: a review

Abstract: Background Globally, adults aged 65 years or older will increase from 516 million in 2009 to an estimated 1.53 billion in 2050. Due to substance use at earlier ages that may continue into later life, and ageingrelated changes in medical conditions, older substance users are at risk for substance-related consequences.Methods MEDLINE and PsychInfo databases were searched using keywords: alcohol use disorder, drug use disorder, drug misuse, substance use disorder, prescription drug abuse, and substance abuse. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(86 citation statements)
references
References 45 publications
2
77
0
2
Order By: Relevance
“…Giving the rising prevalence of illicit stimulant use among older adults [1], it is possible this condition might occur more often in the future. More attention should be paid to this upcoming cause of neurocognitive disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giving the rising prevalence of illicit stimulant use among older adults [1], it is possible this condition might occur more often in the future. More attention should be paid to this upcoming cause of neurocognitive disorder.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of illicit substance use among older adults is rising [1], partly as a consequence of the aging of the baby boom generation (born between 1946 and 1964), as within this cohort, drug use during youth has been found to be significantly higher compared to earlier cohorts [2]. It is likely this will be accompanied by greater risks to the older adult, because of age-related changes in drug metabolism and neurotransmitter systems mediating drug effects in the brain [3].…”
Section: Introductionmentioning
confidence: 99%
“…Misuse and diversion may be associated with mental health problems: in the United States, a review of public databases found that 3% of adults older than 50 years receiving outpatient psychiatric treatment used illicit drugs, and that drug users in methadone maintenance treatment exhibited multiple psychiatric or medical conditions [24]. A majority of mental health professionals perceive non-compliance in patients diagnosed with both a mental illness and a substance addiction (dual diagnosis).…”
Section: Resultsmentioning
confidence: 99%
“…13 Psychiatric patients may be especially vulnerable to the potential hazardous outcomes of misuse of controlled substances, possibly secondary to existing substance abuse comorbidities or lack of knowledge leading to failure to disclose the use of controlled substances. [14][15][16] In such cases, potential side effects and interactions among certain medications may not be evaluated by prescribers and pharmacists. To raise awareness among psychiatric service providers about the importance of safe prescribing practices and proactive use of PDMP databases, we examined the prevalence of nondisclosure and/or abuse of controlled substances among the psychiatric outpatients in the Los Angeles County+University of Southern California (LAC+USC) health care system in Los Angeles California by reviewing data from the CURES database.…”
mentioning
confidence: 99%